The Effect of Lateral Pharyngeal Collapse Patterns on Therapy Response in Upper Airway Stimulation Surgery. (September 2021) - Flynn, John; Boyd, Christopher; Yalamanchali, Sreeya; Rouse, David; Goodwin, Sara; Penn, Joseph; Larsen, Christopher
Objectives: Obstructive sleep apnea (OSA) is characterized by repeated upper airway collapse while sleeping which leads to intermittent hypoxemia. Upper airway stimulation (UAS) is a commonly practiced modality for treating OSA in patients who cannot tolerate, or do not benefit from, positive airway pressure (PAP). The purpose of this study is to identify the effect of lateral pharyngeal collapse patterns on therapy response in UAS. Methods: A retrospective cohort study from a single, tertiary-care academic center was performed. Patients who underwent UAS between October 2016 and July 2019 were identified and analyzed. Drug-induced Sleep Endoscopy (DISE) outcomes between Apnea-Hypopnea Index (AHI) responders and AHI non-responders were compared. Those with complete concentric collapse at the velopharynx were not candidates for UAS. Results: About 95 patients that underwent UAS were included in this study. Pre- to Post-UAS demonstrated significant improvements in Epworth Sleepiness Scale (12.0 vs 4.0, P = .001), AHI (29.8 vs 5.4, P < .001) and minimum oxygen saturation (79% vs 83%, P < .001). No DISE findings significantly predicted AHI response after UAS. Specifically, multiple types of lateral pharyngeal collapse patterns did not adversely effect change in AHI or AHI response rate. Conclusion: Demonstration of lateral pharyngeal collapse on DISE, in the absence of complete concentric velopharyngeal obstruction, does not appear to adversely affect AHI outcomes in UAS patients. Level of Evidence: VI